BORU GİRİŞİNDE ENJEKTÖRLÜ TÜRBÜLANS ÜRETİCİSİ BULUNAN ISI DEĞİŞTİRİCİLERİNDE ISI TRANSFERİNİN VE BASINÇ DÜŞÜŞÜNÜN İNCELENMESİ - ÇAKMAK, GÜLŞAH (Fırat Üniveristesi, 2000)
Yüksek Lisans Tezi BORU GİRİŞİNDE ENJEKTÖRLÜ TÜRBÜLANS ÜRETİCİSİ BULUNAN ISI DEĞİŞTİRGEÇLERİNDE ISI TRANSFERİNİN VE BASINÇ DÜŞÜŞÜNÜN İNCELENMESİ Gülşah ÇAKMAK Fırat Üniversitesi Fen Bilimleri Enstitüsü Makine Mühendisliği Anabilim Dalı 2000, Sayfa: 100 Bu çalışama da konsantrik tip ısı değiştirgeçlerinde ısı transferinin iyileştirilmesi amacıyla iç borunun giriş bölgesine değişik çap ve sayıda düzgün ve üçgen sıralı enjektör(swirl elemanlar) yerleştirilerek sıcak havada swirl hareket oluşturulmuştur. Bu amaçla değişik dönmeli akış üreticileri(enjektörler) deneysel olarak test edilmek için hazırlanmıştır. Bu elemanlar değişik çap ve sayıda enjektör içeren kapak şeklinde olup iç borunun giriş bölümüne kolaylıkla takılıp sökülebilmektedir. Sıcak hava ve soğuk su sırayla iç boru ve annular aralıktan geçmektedir. Deneyler değişik Reynolds Sayılarında zıt ve paralel akışlar için yapılmıştır.IV Deneylerde kullanılan swirl elemanların(enjektör) sayısının artması ve çapının azalmasıyla ısı transferi artmıştır. Ayrıca üçgen sıralı durumda bu iyileşmeler daha fazla olmuştur. En yüksek iyileşme üçgen sıralı, en küçük çaplı, beş sıralı swirl elemanında zıt akışlı ısı değiştirgeci modunda görülmüştür. İç boru girişinde takılan elemanlar nedeniyle meydana gelen basınç kaybı nedeniyle ilave akış enerjisi swirl elemanın ısıl kazancı yanında daha düşük kalmıştır. Elde edilen sonuçlara göre swirl elemanlı ısı değiştirgecinin swirl elemansız ısı değiştirgeci ile kıyaslanmasıyla ısı transferinde % 190 iyileşme olduğu görüldü. İç borunun girişme yerleştirilen bu elemanların kullanılmasıyla aynı kapasitede fakat daha küçük boyutta ısı değiştirgeci elde etmenin mümkün olduğu gösterildi. Anahtar Kelimeler: Isı Değiştirgeci, Dönmeli akış, Enjektör.

SUMMARY Master Thesis THE INVESTIGATION OF HEAT TRANSFER AND PRESSURE DROP TN THE HEAT EXCHANGERS EQUIPPED TURBULANCE GENERATOR WITH IN JEKTOR AT THE ENTRANCE SECTION Gülşah ÇAKMAK University of Fırat Gradute School of Natural and Applied Science Department of Mechanical Engineering 2000, Page: 100 In this work, undertaken to enhance heat transfer rates, swirling motion was imposed on the hot air by placing injektors(swirl elements) with various diameter and number of circular slots in straight or zig-zag line rows on the entrance section of a inner pipe of concentric tube heat exchanger with this aim various swirl generators(injectors) were prepared to test in the experiments. These elements are lid-shaped parts containing different diameter and number of circular slots and can be placed and removed eaisly on the entance section of the inner pipe. Hot air and cold'water were passed though the inner pipe and annulus respectively. Experiments were carried out for both parallel and countercurrent flow models of the fluids at Reynolds numbers.VI Heat transfer rates increased with decresing diameter and with increasing number of slots the swirl elements(injectors) used in the experiments. Additional enhancements aquied with slots arranged in zig-zag line. The highest enhancement was seen to occur in countercurrent flow mode of exchanger with swirl elements having smaller diameter five slots in a row of zig-zag line. The additional flow energy required to overcome the loves in the entrance section of the inner pipe was found to be very much lower than net heat gain aquired with swirl elements. The results showed that up to % 190 enhancement could be accomplished in heat transfer rates with this kind of swirl generators compared to heat exchanger without these elements. In the end of the study, the results showed that a rather smaller size but the same capasity heat exchanger could be proposed by using these elements improsing swirling to the fluid flowing through inner pipe. Key Words: Heat exchanger, Swirling flow, Injector.
The Investigation of heat transfer and pressure drop in the heat exchangers equipped turbulance generator with injektor at the entrance section
Keywords: Makine Mühendisliği; Mechanical Engineering